Kinetics of Competing Reactions of N-aryl-4-chloro-1,8-naphthalimides with Primary Amines - McKenney, Ryan K.; La Plante, Kayla A. (My University, 2012)
This study presented the mechanistic implications of the kinetics of competing reactions of N-aryl-4-chloro-1,8-naphthalimides with primary amines.
Color poster with text, diagrams, tables, and graphs.
Keywords: Chemical kinetics; Naphthalimides; Amines; Posters